1995
DOI: 10.1128/aac.39.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain alkanoylcholines, a new category of soft antimicrobial agents that are enzymatically degradable

Abstract: A new category of amphiphilic hydrolyzable quaternary ammonium compounds with rapid and high levels of antimicrobial activity was studied. The compounds, alkanoylcholines with hydrocarbon chains of 10 to 14 carbon atoms, are hydrolyzed by butyrylcholine esterase, which is present in human serum and mucosal membranes. The hydrolysis products are common components of human metabolism. Alkanoylcholines were tested and found to be active against gram-negative and gram-positive bacteria as well as yeasts. The micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 16 publications
(23 reference statements)
4
46
1
Order By: Relevance
“…For example, the micellar concentrations of quaternary ammonium salts conjugated to alkyl groups are 12,700, 1,790, and 210 M for C12, C14, and C16 alkyl groups, respectively (30). Furthermore, previous studies (38) have also shown that the micellar concentration of hexadecanoic acid conjugated to an amino acid is in a micromolar range and should significantly decrease by increasing the peptidic chain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the micellar concentrations of quaternary ammonium salts conjugated to alkyl groups are 12,700, 1,790, and 210 M for C12, C14, and C16 alkyl groups, respectively (30). Furthermore, previous studies (38) have also shown that the micellar concentration of hexadecanoic acid conjugated to an amino acid is in a micromolar range and should significantly decrease by increasing the peptidic chain.…”
Section: Discussionmentioning
confidence: 99%
“…27). For example, the alkanoylcholines were found active against gram-negative and gram-positive bacteria, as well as yeasts [322]. Activity increased with increasing chain-length and was similar to that of the stable, hard quaternary ammonium compounds of similar length such as hexadecyltrimethylammonium bromide.…”
Section: Environmental-friendly Quaternary Analogsmentioning
confidence: 94%
“…Long-Chain Esters of Betaine and Choline Another, unrelated effort was directed toward the development of long-chain esters (117, 120) of betaine (122) or choline (119) as soft antimicrobial agents (Fig. 27) [321][322][323][324][325]. These compounds are ester-containing structural analogs of amphiphilic quaternary ammonium compounds, which, similar to cetylpyridinium (108), are surface active substances known for their membrane-disruptive and antimicrobial activities.…”
Section: Environmental-friendly Quaternary Analogsmentioning
confidence: 99%
“…Such antimicrobial function is very similar to that determined for QAS. Chitosan can also interact with the DNA of microorganisms to prevent protein synthesis + nontoxicity, biocompatibility and biodegradability − weak adhesion to cellulose fibres, resulting in a gradual leaching from the fibre surface with repetitive washing Metals (Ag, Co, Zn), metal compounds and nanoparticles of metals [20,21] Oxidative stress resulting in damage to the lipids, binding and inactivation of intracellular proteins [22], inhibiting active enzyme centres in microorganisms [16] and losses replication ability of microorganisms DNA + nano-sized inorganic particles possess high surface area/volume ratio and display unique physical and chemical properties Ag: low toxicity to animals' cell [23] Bioactive Plant-based Antimicrobial Agents [24,25] mostly secondary metabolites such as alkaloids, steroids, tannins, and phenol compounds resembling endogenous metabolites, ligands, hormones, signal transduction molecules or neurotransmitters +: enable the production of safe, nontoxic, skin and environment friendly bioactive textile products QAC [26][27][28][29][30] Interactions between the cationic ammonium group of the QAC and the negatively charged cell membrane of the microbe; these interactions consequently result in the formation of a surfactantmicrobe complex. This in turn causes the interruption of all essential functions of the cell membrane: the denaturation of proteins and interruption of protein activity, causing disruption of the cell structure [22] +: active against a broad spectrum of microorganisms such as Gram-positive and Gram-negative bacteria, fungi and certain types of viruses −: QASs have an inherent weakness: leaching from the textile.…”
Section: Properties Of Antimicrobial Textilesmentioning
confidence: 99%